Gambaran Tingkat Kepuasan Pasien Terhadap Pelayanan Fisioterapi di Rumah Sakit Dr Hafiz (RSDH) Cianjur - Ajeng Marshella Sumantri; Roy Daniel Nainggolan; Ronald Erwansyah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Satisfaction is very important in assessing service quality, especially in health services. Physiotherapy services are one of the medical rehabilitation services in hospitals aimed at individuals to restore movement and body functions are required to provide the best service. Dr. Hafiz Hospital (RSDH) Cianjur is the first private hospital in Cianjur, which strives to improve the quality of services in all types of services including physiotherapy services. However, the data on quality indicators of the Physiotherapy Unit showed a decrease in visits. The complaint data that is often received is about administration, service procedures, communication and attitude of officers and others. This study aims to find out the picture of patient satisfaction with physiotherapy services at Dr. Hafiz Cianjur Hospital . This type of research is quantitative with a descriptive method, the population in this study is 87 physiotherapy patients obtained using purposive sampling techniques. Data was obtained using a questionnaire, then the data was processed and univariate analysis. The results showed that satisfaction based on physical evidence (tangible) included high (41.4%), reliability had high satisfaction (41.4%), accuracy (resvonsiveness) had high satisfaction (43.7%), assurance had moderate satisfaction (44.8%), and care (empathy) have moderate satisfaction (47.1%). The hospital is advised to evaluate the quality of service to meet patient satisfaction, so that it can determine the next steps to be taken in measuring wisdom in the future.